If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 + x + -5 = 50 Reorder the terms: -5 + -5 + 4x + x = 50 Combine like terms: -5 + -5 = -10 -10 + 4x + x = 50 Combine like terms: 4x + x = 5x -10 + 5x = 50 Solving -10 + 5x = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = 50 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 50 + 10 5x = 50 + 10 Combine like terms: 50 + 10 = 60 5x = 60 Divide each side by '5'. x = 12 Simplifying x = 12
| log(2)(6X+7)=6 | | 7u+2=5u | | (M-1)(2m-5)=0 | | (6r-7s+8t)-(2r-3s+4t)= | | -7.70=10.8-7.4t | | 24+3n=24+1.5 | | 2x^3-7x^2-8x+28=0factoring | | 5d^2+9d-18=0 | | 7.9a+3.25=-14.13 | | 6x-1+7x=90 | | 7.9a+3.25=-14.1 | | 2x-9y=8 | | 4y=-6x-2 | | X^2-4ix-13=0 | | 6(d+6)-8=2*d+30 | | -51.98=7.7x+5 | | X^2+12=-18 | | (1/2)c=5 | | -1/6z=-4.5 | | 50+90t-4.9t^2=250 | | 3/4-6/8= | | 5.7+1.2n=3.06 | | 8.3y-9.8=13.44 | | 22.1/0.5= | | 3d^2-8d-11=0 | | 6/11p=-12/11 | | (x^3+8)(x^2+5x)=0 | | x^2+48x-1024=0 | | x+26.7=7.1 | | 27+s=23 | | 3x^2-2n-8= | | 3m^2+2m-1=0 |